Genetic diversity in AA and CC genome Oryza species in southern South Asia - Nonnatus S. Bautista etal (Genetic Resources and Crop Evolution (2006) 53: 631-640, 2006)
The CC genome of Oryza is found in nine species of Oryza that are distributed on all continents having a tropical climate. Three diploid Oryza species with CC genome are found in Africa and Asia to Papua New Guinea. In southern South Asia these three CC genome diploid species can be found, O. eichingeri and O. rhizomatis in Sri Lanka and O. officinalis in India. AA genome wild relatives of rice are also found in the same geographic region. Germplasm of both diploid CC and AA genome Oryza germplasm has recently been collected from Sri Lanka. AFLP analysis was used to compare the genetic diversity of the two Oryza genomes from a similar geographic region in southern South Asia. In addition, the diploid CC Oryza germplasm was also analyzed by RAPD and SSR methodologies and the combined results were analyzed. The results show that in southern South Asia the diploid CC genome species have a high level of genetic diversity compared to the diploid AA genome species. Molecular marker analysis revealed that populations of O. rhizomatis from northern and southeastern Sri Lanka are genetically differentiated. One accession of O. rhizomatis was aligned with O. eichingeri. This accession was collected from the site of O. rhizomatis that is the closest to a population of O. eichingeri. O. eichingeri showed lower genetic diversity than the other two diploid Oryza CC genome species. O. officinalis accessions from Assam, India, and China were genetically less diverged from O. eichingeri and O. rhizomatis than two accessions of O. officinalis from Kerala state, India.